Comparison of NoSQL Database and Traditional Database-An emphatic analysis - M. Sandeep Kumar; Prabhu .J (Society of Visual Informatics, 2018)
A Huge amount of data is manipulated by using the web application, Facebook, Twitter, social sites etc. Most of the data are unstructured data. It is not desirable for storing, performing and analyzing data in the relational database for huge data. It affords way towards performing NoSQL database and uses fully for handling the big data. In this paper, we present the performance in store and query operation in NoSQL database, estimating the performance of both reads and write operation using simple and complex queries. Result represents that comparing Cassandra with relation database, Cassandra outperforms the relation database. Most of the organization used only Hbase and Cassandra for benefit of cost. Comparison Various NoSQL Database, issues while performing NoSQL database.Â